Validation of the Canadian norms for the Alberta In fant Motor Scale for infants in a South African region aged four to twelve months; a Pilot Study - A.E. Manuel; M. Burger; Q.A. Louw (AOSIS, 2012)
The Alberta Infant Motor Scale (AIMS) is a norm referenced,performance based, observational tool that assesses motor developmentin infants from birth up to the age of eighteen months. The AIMS has beenwidely used by researchers and clinicians around the world, but only afew attempts were made to validate the Canadian norms for infants residingoutside Canada.The purpose of the study was to validate the Canadian norms of the AIMSfor infants within the Cape Metropolitan region, South Africa.A longitudinal study was conducted using the AIMS to assess the gross motordevelopment of 67 healthy full term infants at 4, 8 and 12 months respectively.At 4 months the mean percentile ranking was significantly higher than the Canadian norm (p=0.01), while no statisticalsignificant differences were found at 8 and 12 months of age.The AIMS is a valid assessment tool for healthy infants aged 8 and 12 months within the Cape Metropole, SouthAfrica. The infants at four months of age scored higher than the Canadian norm. Further validation which incorporatelarger, random samples are required to enable generalisation of the findings for the South African infant population.